Revisiting the Falklands-Malvinas question : transnational and interdisciplinary perspectives - Mira Delli-Zotti, Guillermo Claudio; Pedrosa, Fernando (Political scientist) (University of London Press : Institute of Latin American Studies, School of Advanced Study, University of London, 2021)
"Almost forty years after the Falklands War, the causes and consequences of the military conflict between Argentina and the United Kingdom in 1982 still reverberate. The archipelago that makes up the Falkland-Malvinas Islands is surrounded by complexities and antagonisms--including controversy around its very name. This book interrogates the conflict with approaches from history, political science, sociology, film, and cultural studies. Additionally, this collection brings together English, Spanish, and Argentine specialists and researchers. It includes testimony from war veterans and exiles, essays on the films of Julio Cardoso, and Argentine patriotism as witnessed in contemporary literature and pedagogy. By taking up these different perspectives, Revisiting the Falklands-Malvinas Question moves beyond traditional approaches to the conflict based on nationalism, geopolitics, or military achievements, leading to a more expansive discussion."--Publisher description